An Empirical Study on the Behaviour of Nifty Index by Examining the Derivative Contract - Savitha, R.; Deepika, S. R. (Indian Journal of Finance, 2013)
The term "Derivative" indicates that it has no independent value, i.e. its value is entirely "derived" from the value of the underlying asset. The basic purpose of it is to transfer the price risk from one party to another, and mitigate the risk arising from the future uncertainty of prices. It is generally used as an instrument to hedge risk, but can also be used for speculative purpose. Prices in an organized derivatives market reflect the perception of the market participants about the future and lead the prices of the underlying to the perceived future level. This research is an attempt to find the efficiency of the sentimental indicators of financial derivatives in predicting the trend of the market (behaviour of NIFTY index). Participants in the stock markets believe that the amount of open interest (OI) in a particular contract has a bearing on the behavior of the price of the contract. This perception is put to test in the present research using the end of the day data (historical data) from August 2011 to February 2012, and examined the correlation between the cumulative percentage changes in open interest and cumulative percent change in the price of future contract of NIFTY index. The put-call ratio (PCR) is widely used by technical analysts as an indicator of the investor sentiment concerning future equity price trends. Many stock market experts cite the put-call ratio as an important indicator of investor sentiment, with a low (high) value indicating excessive optimism (pessimism). It is believed that the ratio is a useful contrarian indicator for future stock market behavior. In the present research paper, the value of the put-call ratio as an indicator of future stock market trend is put to test. The research is further extended towards application and analysis of the stock and option strategies in different market conditions and their pay-off using end of the day (EOD) data.